REGIONAL ASPECTS OF AGRICULTURAL INCOME LEVEL IN VOJVODINA PROVINCE IN FUNCTION OF BASIC PRODUCTION FACTORS - Čobanović, Katarina; Nikolić-Đorić, Emilija; Mutavdžić, Beba (Economics of Agriculture, 2010)
In the present research the analysis of the level of national income in agriculture was done for different districts and municipalities of the Province of Vojvodina. The analysis of the achieved level of national income in agriculture in function of the most important factors was performed on the base of classical form the traditional non-linear regression model of Cobb-Douglas production function with labour and capital as predictors and on the extended form of Cobb-Douglas function which in addition includes the arable areas.